Peningkatan Kapasitas Wali Murid TK dalam Implementasi Menu Gizi Seimbang dalam Kaitannya dengan Perkembangan Kognitif Anak di TK Melati Indah, Pekanbaru, Riau - Joni, Joni; Alim, Melvi; Puspita, Yenda; Hastriati, Ade Yelda (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aims to enhance the capacity of parents at TK Melati Indah, Pekanbaru, in implementing balanced nutrition based on local food to address early childhood obesity and unhealthy lunch box patterns. The method was conducted in four stages: identification and pre-testing, interactive education on "Isi Piringku" (My Plate) menu management, cooking demonstrations using local ingredients (such as catfish), and online mentoring.The results showed a significant increase in parents' knowledge, with average scores rising from 55 (fair) to 88 (excellent). Furthermore, there was a notable behavioral shift, characterized by a decrease in the use of double carbohydrates and improved compliance in including animal protein and vegetables in children's lunch boxes. This program demonstrates that nutritional literacy effectively optimizes local food potential to support children's growth and development during the golden age.